Verbal and Non-Verbal Intercultural Communication Challenges and Strategies - Mirani, Thitan; Ikhsanudin; Sumarni (PROJECT (Professional Journal of English Education), 2025)
This study examines the verbal and non-verbal intercultural communication challenges faced by R, an Indonesian exchange student at UC Davis, and explores the strategies he used to overcome them. Employing a narrative inquiry methodology, the research focuses on R’s lived experiences and investigates how these strategies fostered his intercultural communication competence. The findings reveal that R encountered difficulties related to language diversity, differing communication styles, evolving English language usage, and non-verbal cues such as cultural norms and contextual differences. To address these challenges, he utilized strategies including maintaining language fluency, employing visual aids, and adopting alternative communication methods. These approaches enabled him to navigate communication barriers effectively while fostering cultural adaptability and a deeper understanding of cross-cultural nuances. R’s experiences highlight the significance of adaptive strategies in managing personal space, maintaining mindfulness, and engaging actively in intercultural interactions. The study underscores the importance of these skills in enhancing practical communication abilities and navigating the complexities of intercultural environments. These insights contribute to a broader understanding of how exchange students develop competence in diverse cultural settings, providing valuable implications for educators and program coordinators in supporting intercultural learning.